Tropical Healthcare Epidemiology: Weather Determinants of the Etiology of Bloodstream Infections in a Brazilian Hospital - Castelo Branco Fortaleza, Carlos Magno [UNESP]; Caldeira, Silvia Maria [UNESP]; Moreira, Rayana Goncalves [UNESP]; Akazawa, Renata Tamie [UNESP]; Corrente, Jose Eduardo [UNESP]; Souza, Lenice do Rosario de [UNESP]; Cunha, Antonio Ribeiro da [UNESP] (Univ Chicago Press, 2014)
We studied the influence of weather on the etiology of healthcare-associated bloodstream infections in a hospital in Brazil during the years 2005--2010. Monthly average temperatures were positively associated with higher incidence of gram-negative bacilli as a whole, Acinetobacter baumannii, and Enterobacter species. The same groups presented seasonal behavior in stochastic models.
Keywords: bloodstream infections; gram-negative bacilli; Acinetobacter baumannii; Enterobacter species; seasonality